If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 3 = 6y + 8 Reorder the terms: 3 + 4y = 6y + 8 Reorder the terms: 3 + 4y = 8 + 6y Solving 3 + 4y = 8 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 3 + 4y + -6y = 8 + 6y + -6y Combine like terms: 4y + -6y = -2y 3 + -2y = 8 + 6y + -6y Combine like terms: 6y + -6y = 0 3 + -2y = 8 + 0 3 + -2y = 8 Add '-3' to each side of the equation. 3 + -3 + -2y = 8 + -3 Combine like terms: 3 + -3 = 0 0 + -2y = 8 + -3 -2y = 8 + -3 Combine like terms: 8 + -3 = 5 -2y = 5 Divide each side by '-2'. y = -2.5 Simplifying y = -2.5
| 83-v=274 | | 8.2x-57.4=-24.6 | | 10v+5v=25 | | 15n-25n+8n=18 | | 4g-13=3 | | 3(4z+9)=20-7z | | 24-c=2(3) | | 8y-5y=-27 | | -12n-12=-11n | | (-4v+3)(8v+6)=0 | | 9400=10 | | 9y-4y-14=48.80 | | 8.2x-53.4=-24.6 | | (t)=4t+3t^3+2t-7 | | -28-3n=8+6n | | X/5=33 | | 4v-13=59 | | 7b+8=4b-10 | | 4x+24=17 | | 54c+45d= | | 0=1-3sin(3x) | | 53=28-5(x-1) | | p-2.50=4a+10 | | X+45=77 | | 9x+3-3=0 | | 3x*-5x+2=0 | | 0.1x+.7=3.5 | | 21345/15 | | 4+8(1-9b)=-34 | | X-84=123 | | 0.9=0.3b | | 0.3(3z+7)+4.5=0.4(3z-6) |